2021
DOI: 10.3390/en14133890
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Footprint of Residents’ Housing Consumption and Its Driving Forces in China

Abstract: A large population size and rapid economic growth have resulted in a huge amount of housing consumption in China. Therefore, it is critical to identify the determinants of housing carbon footprint (CF) and prepare appropriate carbon mitigation measures. By employing the IPCC accounting method, input-output analysis and the stochastic impacts by regression on population, affluence, and technology (STIRPAT) model, this study aims to study the spatio-temporal patterns and identify the driving factors of housing C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…Quantifying household indirect and direct energy consumption-demand relationships using IOA is a particularly widely studied topic (Supasa et al, 2017;Singh et al, 2018;Long et al, 2019). In addition, input-output models have established an important role in measuring household carbon emissions, especially in China (Xu L et al, 2021;Tian et al, 2017;Zhang and Lei, 2017). Many studies have confirmed the contribution of IOA models in promoting energy efficiency and in developing energy efficiency policies of household (Stagnitta et al, 2020).…”
Section: Input-output Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantifying household indirect and direct energy consumption-demand relationships using IOA is a particularly widely studied topic (Supasa et al, 2017;Singh et al, 2018;Long et al, 2019). In addition, input-output models have established an important role in measuring household carbon emissions, especially in China (Xu L et al, 2021;Tian et al, 2017;Zhang and Lei, 2017). Many studies have confirmed the contribution of IOA models in promoting energy efficiency and in developing energy efficiency policies of household (Stagnitta et al, 2020).…”
Section: Input-output Approachmentioning
confidence: 99%
“…Large population sizes and rapidly growing economies lead to large energy consumption and carbon emissions in the residential sector (Xu L et al, 2021), which are threatening environmental sustainability. Identifying and analyzing the key drivers affecting household energy consumption (HEC) has proven to be an important step in improving energy efficiency and pursuing sustainable energy strategies .…”
Section: Influencing Factors Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The capital stock of urban-oriented technological progress is estimated by the perpetual inventory method, with 2000 as the base period, of which the total employment and real GDP are derived from the 2010-2020 China Urban Statistical Yearbook. This paper uses 2009-2019 DMSP/OLS data to obtain nighttime light data in 283 cities in China, and uses the method of Xu et al (2020) to calibrate the problem of inconsistent data sources around 2013 [59]. This paper obtains the basic data for calculating the DEA-malmquist index from the China Urban Statistical Yearbook.…”
Section: Data Sourcementioning
confidence: 99%